Black and Minority Ethnic Boys and Custody in England and Wales: Understanding Subjective Experiences through an Analysis of Official Data - Ravinder Barn; Martina Feilzer; Nick Hardwick (Social Sciences, 2018)
Recent years have seen a dramatic shift in youth justice outcomes and a fall in the number of children drawn into the youth justice system in England and Wales. However, it appears that children from some backgrounds have not benefited as much as others from this change. There is a wealth of academic literature on processes of criminalisation, policies, and practices of youth justice and the experiences of children, particularly boys, in custody. However, there is little detailed understanding of how these processes, policies, and practices affect children from different backgrounds. This paper examines the most intrusive aspect of youth justice, namely, custodial sentences. Through an examination of the Inspectorate of Prisons’ reports and associated surveys, this paper seeks to explore black and minority ethnic boys’ perceptions of their experiences of custody.